Cardiovascular diseases patient\'s Quality of Life in Tabriz-Iran: 2018 - Saber Azami-Aghdash; Hojatollah Gharaee; Mir Hossein Aghaei; Naser Derakhshani (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Recently, Cardiovascular Disease (CVD) is one of the most common causes of mortality all around the world. Achieving the high Quality of Life (QOL) is considered to be important for these patients. Therefore, the objective of the present study is to investigate the quality of life among patients with CVD in Tabriz Province. Methods: This study was conducted in Tabriz University of Medical Sciences in 2018. In this study, 180 patients were selected using convenience sampling method. World Health Organizations QOL-brief (WHOQOL-BREF) modified questionnaire was used for data collection. Questionnaire was consisted of 26 questions about different aspects of patients' QOL. Descriptive statistics analysis including frequency, percentage and mean ± standard deviation was used to analyses the data. Independent samples T-test and One Way ANOVA was also used for data analysis by SPSS.16. P-value less than 5% was considered as statistically significant. Results: Most participants (about 80%) were in the age group of 50-69. Among the participants, about 30% of the participants were satisfied with their health status and only 12% expressed that they can afford their needs. Less than half of the participants stated that they are satisfied with their ability in running their daily affairs. Mean (SD) score of QOL among the participants was 81.37 (11.88), with a minimum and maximum of 52 and 105, respectively.  There was statistically significant relationship between age, place of residence, education and income with QOL (p<0.05).QOL Conclusion: The results showed that QOL is low in patients with CVD in Iran. Therefore, further studies are needed on the above-mentioned factors in order to plan for improving the QOL in these patients.